Concept Mapping Strategy through Hybrid Flexible Course: Its Significance toward Student Achievement - K Kiswati; Rosi Anjarwati (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2022)
The pandemic era pushed teachers to switch their teaching methods into online learning. The concept mapping strategy was one of the most effective teaching strategies for teaching English in face-o face mode . Is the concept mapping strategy still effective in online learning mode? This study utilized a quantitative approach to compare the use of concept mapping strategy and conventional strategy. Both classes did the instruction through hybrid flexible course. To obtain the data, test and observation were used. ANCOVA was performed to analyze the data to get the specific data concern to the effect of the strategy to the student grade. The findings showed that in the hybrid flexible course, concept mapping strategy did not impact the students’ achievement, but from the observation, it did impact the students’ motivation and activity during the instruction. It can be concluded that there is no significant difference of using concept mapping strategy and conventional strategy through hybrid flexible course